(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
Starting with Bilinski’s studies on the Giuochi olimpici in Arcadia, this essay aims to delve into the first editions of the competition, which are fundamental for understanding the construction of the Arcadian ideal of improving the past, set in the contemporary querelle des anciens et des modernes. Through the study of the manuscript material preserved in the Biblioteca Angelica, still largely unpublished, was reconstructed the first edition of the Giuochi celebrated in 1697, and then printed with significant variations within the Arcadia crescimbeniana (1708). Subsequently, through comparison with later printings, the points of continuity and change are emphasised, with the aim of highlighting how the competition constitutes a privileged point of view for the study of the relations of the assembly with the context of papal Rome.